1981
DOI: 10.1136/bmj.282.6281.2014
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid arthritis: a psychiatric assessment.

Abstract: Ketotifen overdose: surveillance of the toxicity of a new drug An error occurred in the table of this paper by Drs D B Jefferys and G N Volans (30 May, p 1775). The plasma concentrations of ketotifen should have been expressed in ,ug/l, not mg/I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Similarly, adolescents with asthma tend to report higher levels of psychological stress than adolescents without the disease (29). A few studies have also shown increased susceptibility among individuals with high stress levels to other inflammatory diseases such as rheumatoid arthritis (30) and inflammatory bowel disease (31).…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, adolescents with asthma tend to report higher levels of psychological stress than adolescents without the disease (29). A few studies have also shown increased susceptibility among individuals with high stress levels to other inflammatory diseases such as rheumatoid arthritis (30) and inflammatory bowel disease (31).…”
Section: Discussionmentioning
confidence: 97%
“…There is extensive evidence on stress‐induced alteration, both in immune‐mediated diseases, and in the immune function [7]. A few studies have shown increased susceptibility under stressful circumstances to acute and chronic inflammatory diseases, such as common cold [8], rheumatoid arthritis [9] and inflammatory bowel disease [10]. A positive association between stressful life events and the onset of asthma has been reported in some retrospective studies [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been hypothesized that excessive emotional stress levels and subsequent stress hormone liberation may contribute to RA disease onset due to the potential damage inflicted on the immune system by catecholamines and cortisol (Kumar et al 1981, Rogers et al 1980. RA onset is reported to be associated with recent termination of marriage, recent family death, and loss of employment (King & Cobb 1958, Baker & Brewerton 1981. Schochet (1969) found that the stress factor most often associated with RA onset was 'a threatened or actual loss of a loved one which aroused feelings of rage which the person could not cope with or express'.…”
Section: A Disabling Diseasementioning
confidence: 97%